2011
DOI: 10.5194/aab-54-546-2011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between milk urea, blood plasma urea and body condition score in primiparous browsing goats with different milk yield level

Abstract: The aim of this study was to investigate the relationships among milk urea, blood plasma urea, milk yield and body condition score (BCS) in primiparous goats fed at pasture. Ninety goats of Sarda breed were used and, on the basis of their yield level, divided in three groups of 30 animals each, low (LY), intermediate (IY) and high milk yield (HY). Daily milk yield, milk protein content, milk urea, plasma total protein and albumin, plasma urea and BCS were measured at monthly intervals from 45 days in milking (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Even if statistical differences between the treatments were recorded, blood protein levels were similar to those reported for naturally fed Red Syrian kids by Celi et al (2008) and also creatinine levels were similar to those found in kids of Sicilian breeds (Chiofalo et al, 2004; (Vazzana et al, 2013). Mbassa and Poulsen (1993) reported that urea blood levels are influenced by age with the highest values in young goats, but in the present study urea concentration was lower than that reported for primiparous lactating goats of Sarda breed reared with extensive methods (Pazzola et al, 2011b). Urea levels of Sarda kids, regardless of the feeding treatments, are similar to those recorded by Celi et al (2008) in Red Syrian kids.…”
Section: Tablesupporting
confidence: 86%
See 1 more Smart Citation
“…Even if statistical differences between the treatments were recorded, blood protein levels were similar to those reported for naturally fed Red Syrian kids by Celi et al (2008) and also creatinine levels were similar to those found in kids of Sicilian breeds (Chiofalo et al, 2004; (Vazzana et al, 2013). Mbassa and Poulsen (1993) reported that urea blood levels are influenced by age with the highest values in young goats, but in the present study urea concentration was lower than that reported for primiparous lactating goats of Sarda breed reared with extensive methods (Pazzola et al, 2011b). Urea levels of Sarda kids, regardless of the feeding treatments, are similar to those recorded by Celi et al (2008) in Red Syrian kids.…”
Section: Tablesupporting
confidence: 86%
“…This is due to the good adaptability of the goat, which can exploit pastures not easily accessible to other livestock species, and provide meat, milk and dairy 2009b) and milk production, which is about 20% of the entire amount of goat milk produced in Italy (Pazzola et al, 2011b). Milk from Sarda goats is characterized by a good cheese-making aptitude (Pazzola et al, 2012) which mainly depends on the high protein and fat contents and on the prevalence of "strong" casein genotypes Pazzola et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The higher urea concentration in the blood, the higher amount of urea will be excreted into urine and milk. Because of the high correlation between urea values in blood and milk, and due to easier availability and sample preparation, smaller daily variations and economic cost-effectiveness of the analysis, the method of determining urea concentration in milk has an advantage over its determination in the blood (Chládek and Máchal, 2004;Pazzola et al, 2011).…”
Section: Determination Of Urea Concentration In Milk and Bloodmentioning
confidence: 99%
“…Отож, такі погодні умови як інтенсивність сонячної радіації, сила вітру, температура повітря і вологість повинні враховуватися для оцінювання впливу навколишнього середовища на молочну продуктивність корів. (Mylostyvyi & Chernenko, 2019).…”
Section: вступunclassified